2022
DOI: 10.1186/s12864-022-08667-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and genotype by environment interactions for growth traits in U.S. Red Angus cattle

Abstract: Background Genotypic information produced from single nucleotide polymorphism (SNP) arrays has routinely been used to identify genomic regions associated with complex traits in beef and dairy cattle. Herein, we assembled a dataset consisting of 15,815 Red Angus beef cattle distributed across the continental U.S. and a union set of 836,118 imputed SNPs to conduct genome-wide association analyses (GWAA) for growth traits using univariate linear mixed models (LMM); including birth weight, weaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 139 publications
0
13
1
1
Order By: Relevance
“…Based on a large-scale GWAS using 294,079 first-lactation Holstein cows, BTBD11 (BTB domain-containing 11) was identified as a candidate gene with a major additive effect on the daughter pregnancy rate [ 31 ]. Shi-Yi et al found that ARFIP1 (ADP ribosylation factor-interacting protein 1) is associated with fertility and reproduction traits using whole-genome sequence genotypes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a large-scale GWAS using 294,079 first-lactation Holstein cows, BTBD11 (BTB domain-containing 11) was identified as a candidate gene with a major additive effect on the daughter pregnancy rate [ 31 ]. Shi-Yi et al found that ARFIP1 (ADP ribosylation factor-interacting protein 1) is associated with fertility and reproduction traits using whole-genome sequence genotypes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-quality beef is the breeding target of Qaidam cattle. In the comparison between Qaidam cattle and MG cattle (Supplementary Figure 2B), we observed that the PRKCA, CAMK2D, PHKB, and GRID2 genes (Supplementary Table 5) (V ST value > 0.43) were related to muscle growth and development by searching previous research studies (31)(32)(33)(34). Moreover, we identified PTPRT, BOLL, PLIN4, and ADGRL3 gene regions in the CNVRs of the top V ST values which have obvious copy number differences between Qaidam cattle and MG cattle (Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
“…The BovineSNP50 chứa gần 54.000 dấu phân tử đa hình đơn nucleotide (single nucleotide polymorphism) dọc theo bộ gene của bò (Matukumalli et al, 2009). Gần đây, nhờ vào sự phát triển vượt trội của công nghệ giải trình gene thế hệ mới, và phương pháp nghiên cứu liên kết toàn hệ gene (Genome Wide Association Study), nhiều microarray đã được phát triển và sử dụng với mục đích chọn lọc gene marker: như GeneSeek GGP-LDv3, GeneSeek GGP-LDv4, GeneSeek GGP-90KT, GeneSeek GGP-HDv3, GeneSeek Bovine-GGP-F250, and Illumina HD 778K (Crum et al, 2019;Smith et al, 2022). Bằng việc chọn lọc con giống bằng kiểu gene đã mang lại nhiều giá trị như tăng tính chính xác của chọn lọc thông qua các thông tin liên quan trực tiếp đến kiểu gene, đồng thời rút ngắn thời gian chọn giống so với lai tạo thông thường.…”
Section: Hình 1 Sơ đồ Mô Tả Các Thế Hệ ứNg Dụng Cryobank Và Công Nghệ...unclassified